The pediatric solid organ transplant experience with COVID‐19: An initial multi‐center, multi‐organ case series. (9th November 2020) - Goss, Matthew B.; Galván, N. Thao N.; Ruan, Wenly; Munoz, Flor M.; Brewer, Eileen D.; O'Mahony, Christine A.; Melicoff‐Portillo, Ernestina; Dreyer, William J.; Miloh, Tamir A.; Cigarroa, Francisco G.; Ranch, Daniel; Yoeli, Dor; et al.
Abstract: The clinical course of COVID‐19 in pediatric solid organ transplant recipients remains ambiguous. Though preliminary experiences with adult transplant recipients have been published, literature centered on the pediatric population is limited. We herein report a multi‐center, multi‐organ cohort analysis of COVID‐19‐positive transplant recipients ≤ 18 years at time of transplant. Data were collected via institutions' respective electronic medical record systems. Local review boards approved this cross‐institutional study. Among 5 transplant centers, 26 patients (62% male) were reviewed with a median age of 8 years. Six were heart recipients, 8 kidney, 10 liver, and 2 lung. Presenting symptoms included cough (n = 12 (46%)), fever (n = 9 (35%)), dry/sore throat (n = 3 (12%)), rhinorrhea (n = 3 (12%)), anosmia (n = 2 (8%)), chest pain (n = 2 (8%)), diarrhea (n = 2 (8%)), dyspnea (n = 1 (4%)), and headache (n = 1 (4%)). Six patients (23%) were asymptomatic. No patient required supplemental oxygen, intubation, or ECMO. Eight patients (31%) were hospitalized at time of diagnosis, 3 of whom were already admitted for unrelated problems. Post‐transplant immunosuppression was reduced for only 2 patients (8%). All symptomatic patients recovered within 7 days. Our multi‐institutional experience suggests the prognoses of pediatric transplant recipients infected with COVID‐19 may mirror those of immunocompetent children, with infrequent hospitalization and minimal treatment, if any, required.